Study of Prevalence and Detection of Ectoparasites in Domestic Cats in Al-Qadisiya Province - Firas Hachim Naser; najim Abd Al- waheid Al - Jadoa (Al-Qadisiyah Journal of Pure Science, 2018)
The present study was include investigation of 96 domestic cats which collected from eight regions in Al-Diwanyia province (Diwanyia district, Afak district, Eastern Hamza district, Al-Shamia district, Alasdair township, Sunnia township, Dagharah township, Shaafa' township), from October until September 2016, by using special traps which designed in this study. The study aimed to investigation for external and study of prevalence, severity, distribution of parasites according to months of years, relationship of sex and age of cats, relationship of regions on prevalence of parasites infestation. The study results were appeared infestation 45 cat (46.8%) and included fleas (Ctenocephalides felis) in (37.5%), Hard ticks (Rhipicephalus sanguineus ) in (19.7%). while, There is not found lice and mites in the present study. The relationship of cats sex has shown no significant effect between male and female cats at probability level (P <0.05). The relationship of cats age has shown significant differences between the mature and immature cats at probability level (P <0.05), while, significant differences in Ectoparasites infestation at probability level (P <0.05). while the occurrence of parasite infestation according to regions was shown no significant differences at probability level (P <0.05). The seasons of year were appeared significant effect in Ectoparasites at probability level (P <0.05) during the four seasons.In conclusion, The present study has important role on public health by identification of parasitic species that may be transmitted by  domestic cats in to humans as well as in to domesticated animals.